Identification of Factors Influencing Gentrification: A Case Study in Solo, Indonesia - Satriyono, Raden Danang Aryo Putro; Bayuaji, Luhur (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Indonesia is a country with the highest social gap in Asia. This significant social gap drives the phenomenon of gentrification in several cities in Indonesia. Despite the rise in gentrification occurrences, there is very little research concerning the factors contributing to gentrification behaviors in Indonesia. This study investigates the factors contributing to gentrification in the Kerten Area, Solo, Indonesia, and its social effects. Solo area was selected because many regions in Solo are rapidly developing and attracting residential newcomers from various regions in Indonesia. This study delves into the factors influencing residents' intentions and behavior related to gentrification. The study incorporates variables from the extended Theory of Planned Behavior (TPB) associated with human behavior and perception, such as subjective norms, perceived behavioral control, economic factors, social factors, and social awareness. The survey method was employed with 320 respondents, and the analysis utilized Structural Equation Modeling (SEM). The findings indicate that five variables—subjective norms, social awareness, and economic factors—have a substantial effect on gentrification. This research also discovered that attitude and individual concern factors had no significant effect. These results highlight the importance of managing gentrification to minimize social and community impacts.